Does trace element composition of bivalve shells record utra-high frequency environmental variations?. (June 2020) - Poitevin, Pierre; Chauvaud, Laurent; Pécheyran, Christophe; Lazure, Pascal; Jolivet, Aurélie; Thébault, Julien
Abstract: Saint-Pierre and Miquelon (SPM) is a small archipelago where instrumental measures based on water column velocity and temperature profiles compiled comprehensive evidence for strong near-diurnal (25.8h) current and bottom temperature oscillations (up to 11.5 °C) which is possibly the largest ever observed — at any frequency — on a stratified mid-latitude continental shelf. The main objective of our study was to identify if Placopecten magellanicus can record on its shell these high frequency environmental variations. To this end, we have tried to identify proxies for water temperature and food availability through development of a new ultra-high resolution LA-ICPMS analyses method capable of resolving shell surface elemental composition with a 10 μm resolution. This method was applied on two shell fragments, both representing the third year of growth and 2015 annual growth period, respectively coming from two environmentally contrasted sites, more (30 m depth) or less (10 m depth) affected by high frequency thermal oscillations. Our results strongly suggest a relationship between phytoplankton biomass and barium incorporation into P. magellanicus shells at both sites. Even if P. magellanicus might present a physiological control of magnesium incorporation, the shape of the two Mg/Ca profiles seems to illustrate that temperature also exerts a control on magnesium incorporation in P. magellanicus shells from SPM. While U/Ca and Mg/Ca profiles show a strong positive correlation for 30 m site shell, suggesting that uranium incorporation in P. magellanicus shell is at least partially temperature dependent. The absence of such correlation for 10 m site shell suggests differences in uranium environmental availability or in P. magellanicus biomineralization between these two sites. The resolution of this new analytical method raises questions about such data interpretation related to P. magellanicus growth dynamics and physiology or individual scale based environmental measurements. Highlights: A new method to resolve shell elemental composition with a 10 μm resolution. Ba/Ca of Placopecten magellanicus shell seem to be related to phytoplankton dynamic. Mg/Ca and U/Ca of P. magellanicus shell seem partially temperature dependent. This species might also present a physiological control on Mg and U incorporation. This method may contribute to a better understanding of ion incorporation in shells.